PEMERIKSAAN TEKANAN DARAH DAN SOSIALISASI HIPERTENSI DI DESA SUNGAI RAYA - Devy Rahmadhani; Lisastri Syahrias; Syafiqah Fakhirah; Safitri Safitri; Eka Novia Rahmawati (Jurnal Pengabdian Ilmu Kesehatan, 2022)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal as expressed by systolic (top) and diastolic (bottom) numbers when a blood pressure check is carried out with a sphygmomanometer (mercury cuff) in the form of a blood pressure monitor, or other digital device. Hypertension is defined as high blood pressure, systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg and having a history of hypertension. An understanding of the complications of hypertension and the prevention of hypertension that arises and is caused by a lack of patient knowledge. If the knowledge about hypertension is good enough, it will affect the lifestyle of people with hypertension.